MANAGEMENT FISIOTERAPI PADA KASUS MULITPLE LIGAMENT KNEE INJURY E.C POST RECONSTRUCTION ANTERIOR CRUCIATUM LIGAMENT, POSTERIOR CRUCIATUM LIGAMENT DAN MEDIAL COLLATERAL LIGAMENT DENGAN PERUBAHAN GAIT PATTERN: A CASE REPORT - Yuni Sandra Repisalta; Dwi Rosella Komalasari; Arik Dwindayani (Bajang Institute, 2023)
ackground: Multiple ligament knee injury (MLKI) is a very complex injury. MLKI affects the anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), medial collateral ligament (MCL) and lateral collateral ligament (LCL). Disorders that occur in MLKI cause a decrease in ROM, decreased muscle strength, muscle atrophy, decreased ability to function, accompanied by balance disorders and changes in gait patterns. Purpose: To determine the effectiveness of physiotherapy management with NMES, OKCE, CKCE, and MCE in patients with MLKI e.c post reconstruction ACL, PCL, and MCL accompanied by changes in gait patterns. Methods: This study uses a case report study with analysis and evaluation of 3 meetings in 3 weeks. Outcome: Using the results of measurements with a goniometer on ROM, manual muscle test (MMT) on muscle strength, anthropometry with midline on muscle atrophy. The results of the assessment of functional activity ability used the western ontario and mcmaster universities osteoarthritis (WOMAC) index, balance analysis using the single leg stance test (SLST) and timed up and go test (TUG) as well as phases of gait analysis on changes in gait patterns. Conclusion: This study is to determine the effectiveness of physiotherapy management with NMES, OKCE, CKCE, and MCE which is used for rehabilitation programs in patients diagnosed with MLKI e.c post reconstruction of ACL, PCL, and MCL accompanied by changes in gait patterns. Administration of the NMES, OKCE, CKCE, and MCE programs increases ROM, increases muscle strength, increases muscle mass, and improves ability to perform functional activities. This program also shows that balance and gait patterns are getting better.